Challenges and Prospects of Virtual Reality and Augmented Reality Utilization among Primary School Teachers: A Developing Country Perspective - Alalwan, Nasser; Cheng, Lim; Al-Samarraie, Hosam; Yousef, Reem; Ibrahim Alzahrani, Ahmed; Sarsam, Samer Muthana (Studies in educational evaluation, 2020)
•School teachers have been criticized to have insignificant knowledge about using virtual reality (VR) and augmented reality (AR).•The utilization of VR and AR among school teachers was investigated.•The key challenges and prospects of VR and AR utilization were addressed.•Teachers’ perceptions on requirements for using VR are more difficult to comply with, as compared to those for AR. The concepts of virtualization for facilitating learning have become the focus of attention in several countries. Yet, the limited understanding of how technologies such as augmented reality (AR) and virtual reality (VR) can be used to improve the learning and teaching of science makes it difficult for educational policy makers to apply additional measures in order to ensure the availability of equipment and trained staff. A semi-structured interview was used to gather data from primary school teachers about the challenges and prospects of utilizing VR and AR technologies in teaching science subjects. A set of evidence and recommendations on AR and VR utilization for teaching science were provided based on an interview of 29 science teachers. It was determined that lack of competency, limited instructional design, lack of focused attention, lack of time, and limited environmental resources were common challenges in VR and AR utilization. In addition, we found that both technologies can be used to promote exploratory behavior and perceived usefulness and develop a positive attitude. Other findings related to these aspects were identified and described. The outcomes from this study can provide insights for administrators and policy makers to set priorities for using VR and AR in school practice to carry out various reflective and exploration tasks.